2014
DOI: 10.1182/blood-2014-04-570770
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytomagenesis in Eμ-v-abl transgenic mice is accelerated when apoptosis is restrained

Abstract: Key Points• Loss of Bim accelerated the development and increased the incidence of plasmacytomas in Em-v-abl transgenic mice.• As in multiple myeloma, elevated expression of myc and cyclin D genes was common and p53 deregulation was rare.Mice susceptible to plasma cell tumors provide a useful model for human multiple myeloma. We previously showed that mice expressing an Em-v-abl oncogene solely develop plasmacytomas. Here we show that loss of the proapoptotic BH3-only protein Bim or, to a lesser extent, overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 76 publications
(92 reference statements)
1
7
0
Order By: Relevance
“…Whereas the p19 Arf /p53 pathway is frequently mutated in tumors arising in Bim +/+ Eμ-Myc mice, it was unaffected in most Bim-deficient tumors, indicating that Bim reduction is an effective alternative to loss of p53 function [ 480 ]. Similarly, Bim deficiency in mice overexpressing the Eμ-vAbl oncogene accelerated the development of plasmacytomas [ 481 ]. The v-Abl-expressing plasmacytomas frequently harbor a rearranged c-Myc gene [ 481 ].…”
Section: Physiological and Pathophysiological Aspects Of Bimmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the p19 Arf /p53 pathway is frequently mutated in tumors arising in Bim +/+ Eμ-Myc mice, it was unaffected in most Bim-deficient tumors, indicating that Bim reduction is an effective alternative to loss of p53 function [ 480 ]. Similarly, Bim deficiency in mice overexpressing the Eμ-vAbl oncogene accelerated the development of plasmacytomas [ 481 ]. The v-Abl-expressing plasmacytomas frequently harbor a rearranged c-Myc gene [ 481 ].…”
Section: Physiological and Pathophysiological Aspects Of Bimmentioning
confidence: 99%
“…Similarly, Bim deficiency in mice overexpressing the Eμ-vAbl oncogene accelerated the development of plasmacytomas [ 481 ]. The v-Abl-expressing plasmacytomas frequently harbor a rearranged c-Myc gene [ 481 ]. Another example is the formation and growth of tumors derived from baby mouse kidney epithelial (BMK) cells transformed by E1A and dominant negative p53, that is facilitated by simultaneous Bim deficiency [ 482 ], suggesting a role for Bim in preventing epithelial cancer cell formation.…”
Section: Physiological and Pathophysiological Aspects Of Bimmentioning
confidence: 99%
“…Although on its own enforced BCL2 expression was incapable of transforming normal cells to full malignancy, its ability to prevent the suicide of oncogenically stressed cells enabled it to potently synergize with conventional growth-promoting oncogenes, such as c-Myc or v-Abl to generate malignant cells both in vitro and in vivo. 5,[7][8][9][10] Because aberrant expression of BCL2 was associated with lymphoma, these experiments linked inhibition of cell suicide with malignancy in humans, implicating a novel oncogenic mechanism. They also provided the first molecular handle into the molecular mechanism of apoptosis, and demonstrated that growth factor receptor-driven promotion of cell proliferation versus cell survival are subject to distinct control, with only the latter affected by BCL2.…”
mentioning
confidence: 99%
“…[21][22][23][24] Conversely, overexpression of MCL-1 enhanced c-MYC-and v-ABL-driven lymphoma and plasmacytoma development, respectively. [25][26][27] Hence, it was hypothesised that inhibitors of MCL-1 (BH3 mimetics) may efficiently kill tumour cells. Excitingly, a potent and highly specific MCL-1 inhibitor, S63845, was recently developed and first evaluations demonstrated great potential against diverse tumours and tolerability in preclinical models of cancer.…”
mentioning
confidence: 99%